EFFECT OF CAPITAL STRUCTURE ON FAILURE OF SOME SELECTED COMMERCIAL BANKS IN NIGERIA - Alhaji, Umaru Abdulmalik; Adamu, Bawa Shuaibu; Isah, Ibrahim; Yusuf, Mohammed Abdullahi; Salisu, Ibrahim Yabagi (Kashere Journal of Management Sciences, 2025)
The study explores the intricate relationship between capital structure and corporate failure within the context of selected commercial banks in Nigeria. Capital structure, a fundamental aspect of financial management, plays a pivotal role in determining a firm’s risk and resilience. This study delves into how the composition of a bank’s capital, whether it is through debt or equity, impacts its susceptibility to failure in the dynamic Nigerian banking sector. Nigeria’s banking landscape is characterized by various challenges, including regulatory changes, economic volatility, and fierce competition. Against this backdrop, understanding how different capital structures influence banks’ stability is imperative for policymakers, investors, and banking executives alike. By employing a case study approach, the research investigates the capital structures of several commercial banks, analyzing their debt-to-equity ratios, leverage levels, and overall financial health. Through comprehensive data analysis and statistical techniques, the study aims to uncover patterns and correlations between capital structure choices and instances of corporate failure among the selected banks. The findings of this research have significant implications for risk management practices, regulatory frameworks, and strategic decision-making within the Nigerian banking sector. Furthermore, the study contributes to the broader literature on corporate finance and banking by offering insights into the nuanced dynamics of capital structure and its impact on organizational resilience in emerging market contexts. Ultimately, by shedding light on the intricate interplay between capital structure and corporate failure, this research seeks to provide stakeholders with valuable knowledge to navigate the complexities of the Nigerian banking environment and foster greater financial stability and sustainability within the sector.